Critical Analysis of Disputes on Authority Between Institutions In The Constitutional Court - Mahda Rahman (Dinasti Research, 2026)
The purpose of this scientific article is to provide an analysis of the Constitutional Court's authority in deciding when a dispute arises regarding the authority held by state institutions in Indonesia, using sources such as laws and regulations, journals, and online articles whose topics are relevant to this discussion. As is well known, Indonesia, as a state of law, always bases everything on written law, as well as on the Constitutional Court's authority to decide when a dispute arises regarding the authority of state institutions. Regarding the Constitutional Court's authority, it has been regulated by Article 24, Letter C, of the 1945 Constitution and the Constitutional Court Law. However, in practice, these regulations still face many challenges, especially regarding the double interpretation of which institutions have the right to dispute in the Constitutional Court over their authority. So it can be understood that, even though theoretically and legally there are already rules governing the Constitutional Court's authority to decide when a dispute arises regarding the authority of a state institution, more detailed rules are still needed on this matter to prevent ambiguity in interpreting the existing articles.